Barriers to recruitment, retention and intervention delivery in a randomized trial among patients with firearm injuries - Anthony S. Floyd; Vivian H. Lyons; Lauren K. Whiteside; Kevin P. Haggerty; Frederick P. Rivara; Ali Rowhani-Rahbar (BMC, 2021)
Abstract Background We discuss barriers to recruitment, retention, and intervention delivery in a randomized controlled trial (RCT) of patients presenting with firearm injuries to a Level 1 trauma center. The intervention was adapted from the Critical Time Intervention and included a six-month period of support in the community after hospital discharge to address recovery goals. This study was one of the first RCTs of a hospital- and community-based intervention provided solely among patients with firearm injuries. Main text Barriers to recruitment included limited staffing, coupled with wide variability in length of stay and admission times, which made it difficult to predict the best time to recruit. At the same time, more acutely affected patients needed more time to stabilize in order to determine whether eligibility criteria were met. Barriers to retention included insufficient patient resources for stable housing, communication and transportation, as well as limited time for patients to meet with study staff to respond to follow-up surveys. These barriers similarly affected intervention delivery as patients who were recruited, but had fewer resources to help with recovery, had lower intervention engagement. These barriers fall within the broader context of system avoidance (e.g., avoiding institutions that keep formal records). Since the patient sample was racially diverse with the majority of patients having prior criminal justice system involvement, this may have precluded active participation from some patients, especially those from communities that have been subject to long and sustained history of trauma and racism. We discuss approaches to overcoming these barriers and the importance of such efforts to further implement and evaluate hospital-based violence intervention programs in the future. Conclusion Developing strategies to overcome barriers to data collection and ongoing participant contact are essential to gathering robust information to understand how well violence prevention programs work and providing the best care possible for people recovering from injuries. Trial registration ClinicalTrials.gov NCT02630225 . Registered 12/15/2015.